1990
DOI: 10.1037/0022-0663.82.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Training the word recognition skills of reading disabled children: Treatment and transfer effects.

Abstract: Fifty-four disabled readers were randomly assigned to one of two word recognition and spelling training programs or to a problem solving and study skills training program. One word-training program taught orthographically regular words by whole word methods alone; the other trained constituent grapheme-phoneme correspondences. The word-training groups made significant gains in word recognition accuracy and speed and in spelling. Significant transfer was observed on uninstructed spelling content but not on unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
3
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 31 publications
3
64
3
3
Order By: Relevance
“…One of the most important results of the present study was that it was possible to achieve generalization from sublexical level to words containing the sub-lexical items, as the interventions were associated with better learning of the transfer words than the control condition. In training programs focused on reading fluency, generalization effects to untrained material have not been widely evaluated (Berends and Reitsma 2006b), and in the few studies in which generalization has been examined, the effects have been low or absent (e.g., Berends and Reitsma 2006a, b;Lemoine et al 1993;Lovett et al 1990;Martin-Chang et al 2007;Thaler et al 2004). Typically, the results of repeated word naming studies have indicated that the effects of training are item specific; that is, the repetition of words enhances word-specific orthographic representations (e.g., Berends and Reitsma 2006b;Kuhn and Stahl 2003;Thaler et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the most important results of the present study was that it was possible to achieve generalization from sublexical level to words containing the sub-lexical items, as the interventions were associated with better learning of the transfer words than the control condition. In training programs focused on reading fluency, generalization effects to untrained material have not been widely evaluated (Berends and Reitsma 2006b), and in the few studies in which generalization has been examined, the effects have been low or absent (e.g., Berends and Reitsma 2006a, b;Lemoine et al 1993;Lovett et al 1990;Martin-Chang et al 2007;Thaler et al 2004). Typically, the results of repeated word naming studies have indicated that the effects of training are item specific; that is, the repetition of words enhances word-specific orthographic representations (e.g., Berends and Reitsma 2006b;Kuhn and Stahl 2003;Thaler et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Previous training studies have revealed that repetitions of words or pseudowords can enhance the reading speed of poor readers (Berends and Reitsma 2006a, b;Judica et al 2002;Lemoine et al 1993;Levy et al 1999;Martin-Chang and Levy 2005;Thaler et al 2004;Wentink et al 1997). However, when this kind of training has been targeted at the poorest readers, they have not attained the level of average readers (e.g., Thaler et al 2004), or the generalization effects have been low (e.g., Berends and Reitsma 2006a, b;Lemoine et al 1993;Lovett et al 1990;Martin-Chang et al 2007;Thaler et al 2004).…”
mentioning
confidence: 98%
“…The training studies on the repeated reading of single words have revealed that repetitions of words or pseudowords can enhance the reading speed of poor readers (Berends & Reitsma, 2006;Judica, De Luca, Spinelli, & Zoccolotti, 2002;Lemoine, Levy, & Hutchinson, 1993;Levy, Bourassa, & Horn, 1999;Martin-Chang & Levy, 2005;Thaler et al, 2004;Wentink, van Bon, & Schreuder, 1997). However, when this kind of training has been targeted at the poorest readers, they have not attained the level of average readers (e.g., Thaler et al, 2004), or the effects have been item-specific; that is, no generalization effects have been shown (e.g., Berends & Reitsma, 2006;Lemoine et al, 1993;Lovett, Warren-Chaplin, Ransby, & Borden, 1990;Thaler et al, 2004). If the repeated reading of words does not lead to generalization effects, this type of training as a remedial one-to-one tutoring program is a time-consuming task.…”
mentioning
confidence: 95%
“…Children must learn the mappings between the phonemes in spoken words and the letters that represent them in print. This has been shown to be an important aspect of early word decoding (Byrne & Fielding-Barnsley, 1989;Lovett, Warren-Chaplin, Ransby, & Borden, 1990;Share, 1995;Torgesen, Wagner, & Rashotte, 1997;Vellutino & Scanlon, 1987). Training in grapheme-phoneme correspondence rules was also found effective in enhancing word decoding accuracy (Ball & Blachman, 1991;Bradley & Bryant, 1983, 1985Bryant & Impey, 1986;Bus & van IJzendoorn, 1999;Cunningham, 1990;Juel, 1988).…”
mentioning
confidence: 94%